Design Substrate Integrated Waveguide Slot Array Antenna At X-Band - Abdel Rahman Ali, Esra’a Mousa (2013)
Substrate integrated waveguide (SIW) is a rectangular dielectric-filled waveguide, which is synthesized in a planar substrate with arrays of metallic vias to realize bilateral side walls and its transitions with planar structures. These vias act as walls of the waveguide supporting current flow, thus allowing for waveguide mode propagation. SIW is suggested for low-loss, low-cost and high density integration applications. SIW preserves the advantages from both the traditional rectangular waveguide and microstrip for easy integration. It is used in designing passive circuits such as resonators, couplers, filters, power dividers, circulators, and antennas. In this thesis substrate integrated waveguides were investigatedand their application as a slotted waveguide antenna. The standard slotted waveguide antenna is designed following Elliot's modified design procedure. Elliot's modified design procedure takes into account the effects of mutual coupling from the neighboring slots in the array. The antenna is then converted to a slotted SIW antenna by carefully placing two rows of metallic via holes to simulate the sidewalls of the rectangular waveguide. The size and location of the via holes are calculated such that they contain the electromagnetic fields inside the SIW with negligible leakage loss and that the SIW has the same propagation constant and characteristic impedance as its equivalent rectangular waveguide. The antenna is fed by a microstrip line, microstrip line is one of the most popular types of planar transmission lines primarily because it can be fabricated by photolithographic processes and is easily miniaturized and integrated with both passive and active microwave devices. The SIWis designed on X-band, a good radiation pattern with sidelobes -51.78 dB below the main beam is observed. The antenna has an impedance bandwidth of 280 MHz at the operating frequency of 10 GHz.